Durability of ChAdOx1 nCoV-19 (AZD1222) vaccine and hybrid humoral immunity against variants including omicron BA.1 and BA.4 6 months after vaccination (COV005): a post-hoc analysis of a randomised, phase 1b–2a trial. Issue 3 (March 2023) - Madhi, Shabir A; Kwatra, Gaurav; Richardson, Simone I; Koen, Anthonet L; Baillie, Vicky; Cutland, Clare L; Fairlie, Lee; Padayachee, Sherman D; Dheda, Keertan; Barnabas, Shaun L; Bhorat, Qasim Ebrahim; Briner, Carmen; et al.
Summary: Background: COVID-19 vaccine rollout is lagging in Africa, where there has been a high rate of SARS-CoV-2 infection. We aimed to evaluate the effect of SARS-CoV-2 infection before vaccination with the ChAdOx-nCoV19 (AZD1222) vaccine on antibody responses through to 180 days. Methods: We did an unmasked post-hoc immunogenicity analysis after the first and second doses of AZD1222 in a randomised, placebo-controlled, phase 1b–2a study done in seven locations in South Africa. AZD1222 recipients who were HIV-uninfected, were stratified into baseline seropositive or seronegative groups using the serum anti-nucleocapsid (anti-N) immunoglobulin G (IgG) electroluminescence immunoassay to establish SARS-CoV-2 infection before the first dose of AZD1222. Binding IgG to spike (anti-S) and receptor binding domain (anti-RBD) were measured before the first dose (day 0), second dose (day 28), day 42, and day 180. Neutralising antibody (NAb) against SARS-CoV-2 variants D614G, beta, delta, gamma, and A.VOI.V2, and omicron BA1 and BA.4 variants, were measured by pseudovirus assay (day 28, day 42, and day 180). This trial is registered with ClinicalTrials.gov, NCT04444674, and the Pan African Clinicals Trials Registry, PACTR202006922165132. Findings: Of 185 individuals who were randomly assigned to AZD1222, we included 91 individuals who were baseline seropositive and 58 who were baseline seronegative, in the final analysis. In the seropositive group, there was little change of anti-S IgG (and anti-RBD IgG) or neutralising antibody (NAb) titres at day 42 compared with at day 28. Anti-S (and anti-RBD) IgG geometric mean concentrations (GMCs) were higher throughout in the seropositive compared with the seronegative group, including at day 180 (GMCs 517·8 [95% CI 411·3–651·9] vs 82·1 [55·2–122·3] BAU/mL). Also D614G NAb geometric mean titres (GMTs) were higher in the seropositive group than the seronegative group, as was the percentage with titres of at least 185 (80% putative risk reduction threshold [PRRT] against wild-type–alpha COVID-19), including at day 180 (92·0% [74·0–99·0] vs 18·2% [2·3–51·8). Similar findings were observed for beta, A.VOI.V2, and gamma. For delta, BA.1, and BA.4, NAb GMTs and the proportion with titres above the PRRT were substantially higher in the seropositive compared with seronegative group at day 28 and day 42, but no longer differed between the groups by day 180. Interpretation: A single dose of AZD1222 in the general African population, where COVID-19 vaccine coverage is low and SARS-CoV-2 seropositivity is 90%, could enhance the magnitude and quality of antibody responses to SARS-CoV-2. Funding: The Bill & Melinda Gates Foundation, the South African Medical Research Council, the UK Research and Innovation, the UK National Institute for Health Research, and the South African Medical Research Council. Translation: For the Zulu translation of the abstract see Supplementary Materials section.